025: Enhancing Public Participation Effectiveness: What Works, for Whom, in What Circumstances and Why? - Pagatpatan, Celso P, Jr. (Archīum Ateneo, 2015)
BackgroundThis research sought to understand and explain the factors that generate the effectiveness of public participation in health policy. Researchers consider the role of the contextual factors as well as the participation process, especially participation techniques, to influence significantly the effectiveness of public participation. Although these are important factors to consider, these do not sufficiently explain what works, when and why. Objectives This investigation aimed to: (1) explain the causes of participation effectiveness and ineffectiveness, (2) understand the significance of context in achieving participation effectiveness, (3) understand the evidence of participation effectiveness. It ultimately aimed to contribute to the design of effective public participation practice in the Philippine health sector and elsewhere. Methods This study was conducted in two phases. The first phase was a realist synthesis of existing literature on public participation, which included the analysis of 83 journal articles. The result of this phase was a set of mechanisms and the context within which they worked, which have been shown in the literature to promote effective public participation. The second phase included 32 realist interviews of Philippine government leaders and health practitioners to understand which mechanisms from the realist synthesis were occurring or not present in the Philippine context and why. The synthesis of the two phases developed a refined explanation of the causes of participation effectiveness. Result Five key mechanisms were found in both the realist synthesis and the interviews in the Philippines that generate participation effectiveness: political will, partnership synergy, participative voice, inclusiveness and legitimacy. Political expediency and power-over were found to potentially block the effectiveness of public participation. A significant implication of these mechanisms relates to the crucial role of the discretionary power of public officials in aiming for an effective public participation practice. This study also highlighted the need for active populations as well as a diversity of perspectives as important contexts for these mechanisms to operate. Conclusion This study has highlighted that participation effectiveness in the Philippine health sector and elsewhere is caused by several key underlying mechanisms and the understanding of the significant contextual factors that influence the operation of these underlying mechanisms allows us to determine the appropriate interventions (including the participation techniques) that contribute to the generation of participation effectiveness. In a practical sense, this study has shown that understanding the interactions of the context, mechanism, and outcome can provide a direction for planners and practitioners in the design of an effective participation exercise. It clarified in what circumstances a particular participation intervention or strategy could be effective or ineffective by the activation of a particular mechanism.